Issues of Translating Financial Terms: Equivalence at the Word Level and Collocation level (Arabic-English) - Alje’eam, Hamdi Abdelrasool (Journal of Humanities & Social Sciences, 2023)
Equivalence is one of the challenges that face translators in the field of translation. Since translating economic texts plays a significant role in promoting communication and cooperation with other countries under the umbrella of globalization, the translator plays the key role in this context. This research attempts to investigate the equivalence at and above the word level in transferring economic texts from English into Arabic or vice versa. The study argues that equivalence in rendering the economic texts can be achieved particularly. The study tries to pay attention to the importance of financial translation that has witnessed a sort of disregard as compared with literary texts. This study reveals that bilingual dictioaries herein empoloyed can provide a valuable help to translators in the field. The study adopts Baker’s approach to the translation of economic terms. It argues that equivalence can be targeted successfully in economic terms.
Keywords: translation; translation difficulties; equivalence; technical translation; financial text